Identification and validation of a novel ubiquitination-related gene UBE2T in Ewing’s sarcoma - Qu, Guoxin; Xu, Yuanchun; Qu, Ye; Qiu, Jinchao; Chen, Guosheng; Zhao, Nannan; Deng, Jin (Frontiers in Oncology, 2023)
Ewing's sarcoma (ES) is one of the commonest forms of malignant bone tumors threatening health all over the world among children. However, the molecular mechanisms of the genes and signaling pathways of ES remain unclearly explained. For the sake of identifying candidate genes correlated with the tumorigenicity and development of ES, the GSE45544 and GSE17618 microarray datasets were retrieved and acquired from the GEO (Gene Expression Omnibus database) . Functional enrichment analysis was implemented using the R language package after determining DEGs (Differentially expressed genes). An analysis of the key module was carried out employing STRING and Cytoscape after a protein–protein interaction (PPI) network was built. When normal samples were compared to tumor samples, there were 56 genes downregulated and 131 genes upregulated in all 187 DEGs discovered. The enriched functions and pathways of the DEGs, including cell division, cell cycle, mitotic nuclear division, ovocyte reductional-division, cell proliferation, and pregnendione-mediated ovocyte maturity, were analyzed. 149 nodes and 1246 edges were detected in the PPI network, and 15 core genes were determined on the basis of the degree levels. Kaplan-Meier (analysis of survival rate)indicated that UBE2T was a sign of adverse results for sufferers with ES. Finally, immunohistochemistry(IHC) revealed that UBE2T was overexpressed in Ewing's sarcoma tissues.To summarize, the DEGs and core genes confirmed in this paper provide a new perspective to better comprehend the molecularly process underlying the tumorigenicity and development of ES, and they offer potential target-spots for the diagnosis and remedy of ES.